1999
DOI: 10.1200/jco.1999.17.3.927
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel and Carboplatin in the Treatment of Small-Cell Lung Cancer Patients Resistant to Cyclophosphamide, Doxorubicin, and Etoposide: A Non–Cross-Resistant Schedule

Abstract: Second-line PC in CDE-resistant SCLC patients yields a high response rate and seems non-cross-resistant to CDE. Toxicity was mild in these poor-prognosis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(35 citation statements)
references
References 23 publications
1
32
2
Order By: Relevance
“…Our data differ from those reported by Groen et al (1999) who studied the same combination (AUC 7 carboplatin plus 175 mg/m 2 paclitaxel as 3-h infusion every 3 weeks) as second-line treatment in 34 SCLC patients, most of whom had responded to a previous CDE regimen. Groen and colleagues obtained an impressive 73.5% response rate (with 6% complete responses) and a median survival (3) 1 (2.1) Vomiting (2-3) 6 (12.5) Diarrhoea (2) 1 (2.1) Oral mucositis (2) 2 (4.2) Fatigue (2-3) 15 (31.3) Headache (grade 3) 1 (2.1) Allergy (1-2) 2 (4.2) Skin (1) 1 (2.1) Fever (1) 1 (2.1) Cardiac (1) 1 (2.1) Respiratory (1-2) 3 (6.3) Renal (1) 1 (2.1) Hepatic (4) 1 (2.1) Constipation (1) 6 (12.5) Peripheral neurotoxicity (1-2) 3 (6.3) Central nervous system (1) 1 (2.1) Hair loss (2-3) 20 (41.7) exceeding 7 months.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Our data differ from those reported by Groen et al (1999) who studied the same combination (AUC 7 carboplatin plus 175 mg/m 2 paclitaxel as 3-h infusion every 3 weeks) as second-line treatment in 34 SCLC patients, most of whom had responded to a previous CDE regimen. Groen and colleagues obtained an impressive 73.5% response rate (with 6% complete responses) and a median survival (3) 1 (2.1) Vomiting (2-3) 6 (12.5) Diarrhoea (2) 1 (2.1) Oral mucositis (2) 2 (4.2) Fatigue (2-3) 15 (31.3) Headache (grade 3) 1 (2.1) Allergy (1-2) 2 (4.2) Skin (1) 1 (2.1) Fever (1) 1 (2.1) Cardiac (1) 1 (2.1) Respiratory (1-2) 3 (6.3) Renal (1) 1 (2.1) Hepatic (4) 1 (2.1) Constipation (1) 6 (12.5) Peripheral neurotoxicity (1-2) 3 (6.3) Central nervous system (1) 1 (2.1) Hair loss (2-3) 20 (41.7) exceeding 7 months.…”
Section: Discussioncontrasting
confidence: 56%
“…Paclitaxel has been associated with either carboplatin or cisplatin and, in 3-drug regimens, with etoposide (Hainsworth et al, 1997;Glisson et al, 1999). Carboplatin plus paclitaxel has proved successful as second-line treatment (Groen et al, 1999). There are no studies on the first-line use of this combination.…”
mentioning
confidence: 99%
“…In currently open randomized trials in the United Kingdom, regimens in use as standard control regimens include ACE and PE by the Medical Research Council, and CAV/PE by the London Lung Cancer Group. In North America, PE is widely regarded as standard (Murray 1997), while ACE is considered standard by the European Organization for Research and Treatment of Cancer (Groen et al, 1999). The Textbook of Lung Cancer recently published by the International Association for the Study of Lung Cancer (IASLC) lists the following regimens as commonly used and, by implication, standard: PE, CAV, ACE, and CbE (Carney and Shepherd, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Etoposide plus cisplatin, IP and AMR monotherapy have been demonstrated to be particularly effective in SCLC (18)(19)(20). A previous study indicated that solvent-based paclitaxel plus carboplatin may be active in SCLC that is refractory to the above-based regimens (21). Previous studies have reported that the clinical behavior and prognosis of LCNEC are similar to those of SCLC, and that SCLC-based regimens are effective in patients with LCNEC (22,23).…”
Section: A B Cmentioning
confidence: 92%